Kindergarten Early Childhood Learning Practices in Education Institutions Kindergarten - Suratman, Bayu; Rahnang, Rahnang (AlBanna: Jurnal Pendidikan Islam Anak Usia Dini, 2021)
This article is the result of research related to learning practices conducted in An-Naskhin Mranggen Demak Kindergarten. Implementation of learning using the central model and using cooperative learning strategies. In addition, the learning conducted by teachers also seeks to increase the creativity of early childhood in An-Naskhin Mranggen Demak Kindergarten. In addition, there are challenges for teachers in the implementation of learning that has an impact on the learning process carried out. This research was conducted through qualitative research with descriptive approach where the data were obtained based on interviews and observations at An-Naskhin kindergarten in Mranggen Subdistrict, Demak Regency, Central Java Province.